2003
DOI: 10.1063/1.1535904
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of nuclear magnetic shielding in paramagnetic molecules

Abstract: Articles you may be interested inA fully relativistic method for calculation of nuclear magnetic shielding tensors with a restricted magnetically balanced basis in the framework of the matrix Dirac-Kohn-Sham equationa)Perturbational ab initio calculations of relativistic contributions to nuclear magnetic resonance shielding tensorsWe propose and evaluate first principles methods for calculating the nuclear shielding tensor in open-shell, paramagnetic molecules, dealing with the case of small spin-orbit couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(149 citation statements)
references
References 51 publications
4
143
1
1
Order By: Relevance
“…The results we have presented, which complement other studies, [18][19][20][22][23][24][25][26][27][28] show that DFT calculations should offer a major aid in understanding such spectra with minimal assumptions, for a wide variety of open-shell molecules. Indeed, we were able to show that some literature assignments can be easily corrected in this way.…”
Section: Discussionsupporting
confidence: 88%
“…The results we have presented, which complement other studies, [18][19][20][22][23][24][25][26][27][28] show that DFT calculations should offer a major aid in understanding such spectra with minimal assumptions, for a wide variety of open-shell molecules. Indeed, we were able to show that some literature assignments can be easily corrected in this way.…”
Section: Discussionsupporting
confidence: 88%
“…36,37 These formulas contain the so-called orbital term present in the closed-shell expression 38,39 and several terms accounting for the spin-orbit effects that arise from the electron spin, such as the anisotropic dipolar and the isotropic contact contributions. These studies show that the orbital term of the chemical shielding in open-shell systems is calculated analogously to that in closed-shell systems.…”
Section: B Nuclear Independent Chemical Shifts In Open-shell Systemsmentioning
confidence: 99%
“…While the calculation of NMR properties of closed-shell, diamagnetic molecules is now widely used to aid structure determination [36][37][38][39]43], the corresponding computations for open-shell, paramagnetic species are comparatively less developed. Nevertheless, it has been shown that DFT methods can be used to predict NMR and EPR parameters for a variety of paramagnetic organic, organometallic and inorganic molecules [44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Density Functional Theory Calculations Of the Hyperfine Intementioning
confidence: 99%